Perintisan Taman Baca Tunas Merapi sebagai Upaya Pengembangan Generasi Gemar Membaca di Dusun Druwak Desa Logede Kecamatan Karangnongko Klaten - Eko Didik Widianto; Wahyu Krisna Hidayat; Aris Sugiharto (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
Reading Park in the community is one of the important instruments to support community's need for information and knowledge. This dedication activity aimed to pioneer the development of Reading Park in the hamlet of Druwak. This Reading Park contained a collection of books that could be accessed by the public and had been classified based on its subject. This Reading Park was expected to help the community, especially children and parents in Druwak hamlet, to realize the community of Druwak who like reading, so as to open the perception and orientation of thought towards literacy education.